Acute kidney injury of intravenous colistin sulfate compared with colistimethate sodium: a real-world, retrospective cohort study - Ping Yang; Wuping Shuai; Yuanzhi Ju; Hongping Zhu; Rongrong Wang; Xiaoyang Lu; Saiping Jiang (BMC Infectious Diseases)
Abstract Background The nephrotoxicity associated with polymyxins is a critical safety concern in clinical practice. The aim of this study was to compare the nephrotoxicity of patients treated with colistin sulfate (CS) and colistin methanesulfonate (CMS). Methods Data on inpatients who received intravenous colistin (CS) or colistin methanesulfonate (CMS) for over 72 h were collected from January to December 2023. The primary outcome was the incidence of acute kidney injury (AKI) associated with polymyxins, while the secondary outcome was 30-day all-cause mortality. Furthermore, Cox proportional hazard regression analysis was used to identify the risk factors of polymyxin-induced AKI. Results A total of 291 patients were included in this study. The overall incidence of AKI was significantly higher in patients who received CMS compared to those who received CS in the unmatched cohort (29.70% vs. 7.37%) and in the propensity score matching (PSM) cohort (26.30% vs. 10.00%), respectively. However, 30-day all-cause mortality was significantly higher in the CS cohort than in the CMS cohort before (27.37% vs. 15.84%) and after (33.75% vs. 15.00%) PSM. CMS therapy and a lower baseline estimated glomerular filtration rate (eGFR) were identified as independent risk factors for polymyxin-induced AKI. Conclusions This was the first study to investigate the nephrotoxicity difference between CS and CMS to our best knowledge. In this study, the incidence rate of AKI was significantly lower in the CS cohort compared with the CMS cohort, however, 30-day all-cause mortality rate was significantly higher in the CS cohort than in the CMS cohort. Further validation of these findings requires more prospective multicentre studies with a large sample size.